Variedades de primarización, recursos naturales y diferenciación: el desafío de Sudamérica en la relación con China - Castro, Lucio (2012)
In the last decade, China has transformed in a strategic commercial partner for South America. China is the first or the second largest trade partner for the majority of the economies in the sub-region. However, the trade nexus is dominated by the exchange of a limited number of South American commodities for medium-technology products from China. In contrast, other resource abundant economies, such as Australia, New Zealand, Canada and Thailand, amongst others, have been able not only to diversify but also to increase the level of differentiation of its export basket to China. Why South America has not been able to follow a similar trend? In an attempt to provide some answers to these queries, this article adopts a two fold strategy: first, we compare, and, second, we estimate a simple panel data gravity model aimed at uncovering the determinants of Chinese imports of differentiated resource-intensive products. We find that South America invest less in fixed capital and research and development (R&D), it is endowed with a transport and logistics infrastructure of a poorer quality, and lacks preferential access to the Chinese market in comparison to other resource abundant economies. Additionally, the results of the gravity model suggest that preferential market access, creditto the private sector availability and R&D investment are the main determinantsof Chinese imports of differentiated resource intensive products.